Evaluation of conditions for fermentation of fish offal - Lassén, T. Mikael (Agricultural and Food Science, 1995)
Conditions for the lactic acid fermentation of fish offal were evaluated regarding the effect of substrate concentration (2, 5 and 10% dextrose), preacidification with lactic acid (initial pH of 6.8, to 6.5 or 6.0), and inoculum size of Lactobacillus plantarum (107 , 108 and 109 colony forming units (cfu)/g). pH and lactic acid production were monitored during a two-week storage period. A small-scale silo for fermenting fish offal was also constructed, and measurement of redox potential was evaluated as a means to estimate bacterial growth conditions. The most favourable conditions for fermentation, manifested by a low and stable pH and high lactic acid production, were achieved with an inoculum size of 108 cfu/g and 5% dextrose. Preacidification did not affect final pH. Redox potential was shown to give a reliable estimate of growth conditions for bacteria under anaerobic conditions by rapidly falling to below -550mV in silage with a high lactic acid concentration.